Optical properties and simulated x-ray near edge spectra for Y2O2S and Er doped Y2O2S. (December 2022) - Dimakis, Nicholas; Rodriguez, Eric Baldemar Jr.; Ackaah-Gyasi, Kofi Nketia; Pokhrel, Madhab
Abstract: The electronic and optical properties of Y2 O2 S and its Er +3 doped counterparts at various concentrations are analyzed using density functional theory (DFT) and simulated x-ray near edge (XANES) spectra. Our simulations are complemented by absorption experiments, which show Y2 O2 S:Er +3 light emissions in the visible and near infrared. These emissions correspond to Er f–f intraband transitions. We use DFT and DFT+U to calculate the band structure of the Y2 O2 S and its Er +3 doped counterparts, whereas optical properties are calculated using the independent particle approximation (IPA). The host Y2 O2 S optical properties are also calculated using the random phase approximation (RPA) and the many-body GW0 approximation. Our IPA calculations on the Y2 O2 S:Er +3 reveal transitions in the energy region of the bandgap, which are absent in the host spectrum. These are assigned to Er f–f intraband transitions in the visible and near infrared, by applying a rigid energy shift. Moreover, XANES calculations at the Er M5 -edge reveal a pre-edge broad shoulder in the proximity of the Er 4f band, which is also supportive of the f–f intraband transitions. Graphical Abstract: ga1 Highlights: The Y2 O2 S and Y2 O2 S:Er +3 electronic and optical properties are analyzed using DFT and simulated XANES. Our simulations are complemented by Y2 O2 S:Er +3 absorption experiments, which show Er f–f intraband transitions. We use several approximations to calculate the host Y2 O2 S optical properties, thus testing their validity. The Y2 O2 S:Er +3 optical calculations reveal transitions in the bandgap region, which are absent in the host spectrum. XANES M5 Er edge calculations reveal a pre-edge shoulder around the Er 4f band, supporting f–f intraband transitions.